Ácido Tranexámico disminuye el sangrado intraoperatorio en artroplastia de cadera y rodilla - Salazar Leiva, Luis Homero (2019)
The progressive aging of the population in western societies has led to an increase in joint degenerative pathology. As a consequence, the number of prosthetic replacement surgeries has increased considerably, especially in elderly patients. Tranexamic acid is an antifibrinolytic that decreases bleeding by inhibiting the breakdown of the fibrin clot. Objective: The present academic work serves to determine if the use of tranexamic acid reduces intraoperative bleeding in hip and knee arthroplasty. Material and methods: Experimental study, cases and controls, which was performed in patients operated on for hip and knee arthroplasty, in the Orthopedics and Traumatology service at the Regional Teaching Hospital of Trujillo during the period January 2018 to June 2019. They were studied the following variables; preoperative and postoperative hemoglobin dosing, intraoperative bleeding volume and the use of tranexamic acid. The doses of tranexamic acid used in arthroplasty were 1 and 2 g intravenous bolus. Conclusions and recommendations: The studies reviewed show that the use of tranexamic acid is intravenous or topical, reduces intraoperative bleeding, the number of blood transfusions and hospital stay in operated patients. Numerous studies have shown that tranexamic acid is effective in reducing peri-operative bleeding in prosthetic surgery. However, there is no consensus on the most appropriate dose or its method of administration.